From Metagenomics to Discovery of New Viral Species: Galium Leaf Distortion Virus, a Monopartite Begomovirus Endemic in Mexico - Guevara-Rivera, Enrique A.; Rodríguez-Negrete, Edgar A.; Aréchiga-Carvajal, Elva T.; Leyva-López, Norma E.; Méndez-Lozano, Jesús (Frontiers in Microbiology, 2022)
Begomoviruses (Family Geminiviridae) are a major group of emerging plant viruses worldwide. The knowledge of begomoviruses is mostly restricted to crop plant systems. Nevertheless, it has been described that non-cultivated plants are important reservoirs and vessels of viral evolution that leads to the emergence of new diseases. High-throughput sequencing (HTS) has provided a powerful tool for speeding up the understanding of molecular ecology and epidemiology of plant virome and for discovery of new viral species. In this study, by performing earlier metagenomics library data mining, followed by geminivirus-related signature single plant searching and RCA-based full-length viral genome cloning, and based on phylogenetic analysis, genomes of two isolates of a novel monopartite begomovirus species tentatively named Galium leaf distortion virus (GLDV), which infects non-cultivated endemic plant Galium mexicanum, were identified in Colima, Mexico. Analysis of the genetic structure of both isolates (GLDV-1 and GLDV-2) revealed that the GLDV genome displays a DNA-A-like structure shared with the new world (NW) bipartite begomoviruses. Nonetheless, phylogenetic analysis using representative members of the main begomovirus American clades for tree construction grouped both GLDV isolates in a clade of the monopartite NW begomovirus, Tomato leaf deformation virus (ToLDeV). A comparative analysis of viral replication regulatory elements showed that the GLDV-1 isolate possesses an array and sequence conservation of iterons typical of NW begomovirus infecting the Solanaceae and Fabaceae families. Interestingly, GLDV-2 showed iteron sequences described only in monopartite begomovirus from OW belonging to a sweepovirus clade that infects plants of the Convolvulaceae family. In addition, the rep iteron related-domain (IRD) of both isolates display FRVQ or FRIS amino acid sequences corresponding to NW and sweepobegomovirus clades for GMV-1 and GMV-2, respectively. Finally, the lack of the GLDV DNA-B segment (tested by molecular detection and biological assays using GLDV-1/2 infectious clones) confirmed the monopartite nature of GLDV. This is the first time that a monopartite begomovirus is described in Mexican ecosystems, and “in silico” geometagenomics analysis indicates that it is restricted to a specific region. These data revealed additional complexity in monopartite begomovirus genetics and geographic distribution and highlighted the importance of metagenomic approaches in understanding global virome ecology and evolution.